2011
DOI: 10.1002/etc.626
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in the speciation and bioaccumulation of mercury in an arid subtropical reservoir ecosystem

Abstract: Patterns of spatial variation of mercury and methylmercury (MeHg) were examined in sediments and muscle tissue of largemouth bass (Micropterus salmoides) from Amistad International Reservoir, a large and hydrologically complex subtropical water body in the Rio Grande drainage. The distributions of both Hg and MeHg were compared with environmental and biological factors known to influence production of MeHg. The highest concentrations of total Hg (THg) in sediment were found in the Rio Grande arm of the reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It is well known that Hg in fish can vary widely among Simonin et al, 2008) and even within water-bodies (Becker et al, 2011). This variation is linked to variation in catchment land-cover and land use (Hurley et al, 1995), Hg inputs from catchments and the atmosphere (Grigal, 2002;Harris et al, 2007) and other environmental factors that control methylation and demethylation (Seller et al, 1996;Gilmour and Henry, 1991), MeHg availability (Driscoll et al, 1995), food-web structure and trophic transfer efficiency (Pickhardt et al, 2002;Cabana et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Hg in fish can vary widely among Simonin et al, 2008) and even within water-bodies (Becker et al, 2011). This variation is linked to variation in catchment land-cover and land use (Hurley et al, 1995), Hg inputs from catchments and the atmosphere (Grigal, 2002;Harris et al, 2007) and other environmental factors that control methylation and demethylation (Seller et al, 1996;Gilmour and Henry, 1991), MeHg availability (Driscoll et al, 1995), food-web structure and trophic transfer efficiency (Pickhardt et al, 2002;Cabana et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Extended periods of summer bottom water oxygen depletion during stratification in the deeper sections of Grand Lake may have promoted anoxic conditions in sediments that in turn enhanced Hg methylation. The relatively high [THg] for some species in the Neosho River may reflect conditions in the river sediment, such as higher organic matter and porewater dissolved organic carbon, that can promote Hg methylation 42 . While measurements of Hg speciation in water samples were beyond the scope of this study, another study on Hg fate and transport in Grand Lake found elevated bottom water MeHg in the summer near the transition zone of the lake (beginning of mid Grand section), where the combination of deeper water stratification and particle settling from river inputs may have provided optimal conditions for MeHg enrichment 70 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, across many lakes covering a range of geological settings, pH may vary widely and be a key variable in explaining variations in Hg bioavailability and uptake, whereas within a lake, the range may be too small to observe variations in Hg concentrations as a function of pH. In addition, most studies on Hg biomagnification in lakes and reservoirs in North America were conducted in temperate zones 19, 24, 29, 41 , and relatively few 4244 have focused on subtropical regions despite higher Hg emissions from power plants in these areas 45 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation